If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2)+4(2x-6)=6(x-4)+8(2x+1)
We move all terms to the left:
3(x+2)+4(2x-6)-(6(x-4)+8(2x+1))=0
We multiply parentheses
3x+8x-(6(x-4)+8(2x+1))+6-24=0
We calculate terms in parentheses: -(6(x-4)+8(2x+1)), so:We add all the numbers together, and all the variables
6(x-4)+8(2x+1)
We multiply parentheses
6x+16x-24+8
We add all the numbers together, and all the variables
22x-16
Back to the equation:
-(22x-16)
11x-(22x-16)-18=0
We get rid of parentheses
11x-22x+16-18=0
We add all the numbers together, and all the variables
-11x-2=0
We move all terms containing x to the left, all other terms to the right
-11x=2
x=2/-11
x=-2/11
| 17=8b(3)-10 | | 8/5+2/5x=29/10+3/2x+1/2 | | 2a-4a-10=6 | | 3x-3-2*2x-1=2 | | 4x/5+4=32 | | (X^2)-3/2x+1/2=0 | | 7m=55 | | X^2-3/2x+1/2=0 | | 362–150=150+0.05s–150 | | 3x2=24 | | 5^x-1(5-1)=100 | | y+5÷7=4 | | x+0.06=40680 | | 2a+5=-a-13 | | 6+5a=-9 | | 1.00x+0.06x=40680 | | 6x^2+7x=-3 | | 1.00x+0.6x=40680 | | 2(3^x-3^x-1)=324 | | x+0.6x=40680 | | 5x+4-2(4x-(x-2))=-3 | | 5y+1-3y+6-y=18 | | -4/9p=-8 | | 85x=11700 | | 4(x+-3)+(x+3)=6 | | 4a-10=2a+4 | | x-0.85=117 | | -5/9r=-10 | | -8/7x=-2 | | 0,25x=2,5 | | 8x+2x=570 | | 11x/18-10=1/6+6 |